1979
DOI: 10.1210/jcem-48-2-196
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin Suppression by 3,5-Dimethyl-3′-Isopropyl-LThyronine in Man*

Abstract: The thyromimetic activity of 3,5-dimethyl-3'-isopropyl-L-thyronine (DIMIT), a nonhalogenated thyroid analog, was studied in adult men using suppression of TRH-induced TSH release to assess this activity. In nine men, aged 30-58 yr, the TSH increment after 500 microgram TRH iv was compared to the TSH response to TRH 24 h after oral administration of 1 mg DIMIT. Eight euthyroid subjects had normal baseline TSH levels of 1.5 +/- 0.2 (SE) microunit/ml that fell significantly to 0.7 +/- 0.2 microunit/ml 24 h after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…At the one dose investigated, clearance of DIMIT from plasma ofthe rat appears to be slower than reported for T3 (43). A relatively slow clearance of DIMIT apparently also occurs in adult humans (44). The combination of higher concentrations and slower clearance of DIMIT from the fetal circulation of the rat would favor preferential effects of DIMIT in the fetus.…”
Section: Discussionmentioning
confidence: 71%
“…At the one dose investigated, clearance of DIMIT from plasma ofthe rat appears to be slower than reported for T3 (43). A relatively slow clearance of DIMIT apparently also occurs in adult humans (44). The combination of higher concentrations and slower clearance of DIMIT from the fetal circulation of the rat would favor preferential effects of DIMIT in the fetus.…”
Section: Discussionmentioning
confidence: 71%
“…Thyroid hormones (T4 and T3) Replacement therapy, antigoitrogenic, and anticancer Thyroid hormone analogues (DT4, 471 3′,3′,5-TRIAC, 472 etiroxate-HCI, 473 dimethyl-3 isopropyl-L-thyronine 474 Treatment for cerebrovascular diseases and migraine Dopamine antagonist (pimozide) 254 Neuroleptic α-Noradrenergic blockers 479,480 (phentolamine, thioridazine) Neuroleptic Serotonin antagonists (metergoline, 481 cyproheptadine, 482 methysergide 483 ) Antimigraine and appetite stimulators Serotonin agonist (5-hydroxytryptophan) 463 -Glucocorticoids 484,485 Antiinflammatory, antiimmunosuppressive, and anticancer; reduction of intracranial pressure Acetylsalicylic acid 164 Antiinflammatory, antipyretic, and analgesic Growth hormone 165 * Growth promoting Somatostatin 166 Antineoplastic Octreotide 486 Opiates (morphine, 487 leuenkephalin, 488 heroin 409 ) Analgesic Clofibrate 489 Hypolipidemic Fenclofenac 403,432 Nonsteroidal antiinflammatory drug Bexarotene 490 T cell lymphoma IL-6 443 Biotin 194,195 Immune modulating Interference with biotin-strepavidin complexes DT4, Dextrothyroxine; IL, interleukin; T3, triiodothyronine; T4, thyroxine; TRH, thyrotropin-releasing hormone; TRIAC, triiodothyroacetic acid;…”
Section: Decrease Serum Tsh Concentration And/or Its Response To Trhmentioning
confidence: 99%
“…3, 5-Dimethyl-3'-isopropyl-L-thyronine (DIMIT) has demonstrable thyromimetic activity in many primates (BACHRACH et al, 1983;MELMED et al, 1980;TAMAGNA et al, 1979), and is capable of transplacental movement (COMITE et al, 1978). BACHRACH et al (1983) have recently demonstrated that the administration of DIMIT to 131I-treated mothers prevents the clinical manifestations of cretinism in the fetus using monkeys.…”
mentioning
confidence: 99%